The role of financial recovery in improving the bank's reputation : An analytical study of a sample of private Iraqi banks listed on the Iraqi Stock Exchange for the period (2005-2021) - Ali Ibrahim, Lamyaa (Iraqi Journal for Administrative Sciences, 2024)
The research aims to explain the role of financial recovery in improving the bank’s reputation through financial indicators (rate of return on assets, capital owned to loans, capital owned to deposits), while the reputation of the bank was measured by indicators (age of the bank, book value to market value, Stock return), the research sample consisted of nine commercial banks listed on the Iraq Stock Exchange through their annual reports published on the Iraq Stock Exchange for the period of time 2005-2021, using the statistical program (Microsoft Excel vs. 10, SPSS V. 25. Backward Regression Analysis, and analysis of variance), and the research reached a set of main conclusions, including that the commercial banks in the research sample vary in indicators of banks’ reputation, and thus the research came out with a number of recommendations, the most important of which is the necessity of adhering to financial recovery indicators as a main axis of reform, because they are fundamental to the strategies that It has banking management to solve many financial problems.